Groundwater potential assessment in part of Kavrepalanchowk district using cosine amplitude method (Journal of Nepal Geological Society, 2025)
Groundwater plays a vital role in sustaining agriculture, domestic supply, and ecological balance in Nepal’s mid‑hill regions, where surface water availability is highly seasonal. This study assesses groundwater potential in part of Kavrepalanchowk District using the Cosine Amplitude Method (CAM), a statistical approach that integrates multiple thematic layers to delineate potential zones.In this study, multiple thematic layers such as elevation, slope, aspect, curvature, topographic position index (TPI), topographic wetness index (TWI), drainage density, geology and lineament density, were weighted and combined within a GIS framework to delineate groundwater potential map. The resulting map classified the area into five distinct groundwater potential zones: very low, low, moderate, high, and very high. Among the controlling parameters, lineament density (15.8%) and the Topographic Wetness Index (14.4%) were the most influential parameters, underscoring the critical role of structural features and surface saturation in groundwater occurrence. Other factors such as aspect, drainage density, and elevation contributed significantly, while geology and curvature exhibited comparatively lower influence. These findings demonstrate that geomorphological and hydrological factors exert greater control over groundwater potential than lithological characteristics in the study area. The outcomes provide a scientific basis for prioritizing recharge interventions and developing effective groundwater management strategies.